The Contribution of Water and Sunlight to the Lettuce Production - Amaluddin, La Ode; Hildayanti, Hildayanti; Eso, Rosliana; Musyawarah, Rahma; Sugiarto, Agus; Shrestha, Rajendra Prasad; Ramadhan, Muhammad Isa; Sejati, Andri Estining (SOCA: Jurnal Sosial Ekonomi Pertanian, 2023)
Indonesian lettuce production is still lower than consumption. Lettuce production in Indonesia is still low because hydroponic cultivation needs more concern with the water and sunlight factors. This first study aimed to determine the contribution of water and sunlight to the growth of lettuce. The second study aimed to find out the difference in lettuce production between the difference in water and sunlight conditions. This research used the experimental method. The research was conducted in a field laboratory and hydroponic village at the Faculty of Agriculture, Halu Oleo University. Data collection methods using field observations and measurements. The first objective data analysis techniques described water quality and sunlight measurements. The second objective data analysis used a description of the result of the lettuce variable costing. The results showed that water and sunlight contributed to the production of lettuce. The water adds nutrients, and the sunlight does not direct to lettuce-affected plants, which tend to have broad and healthy leaves. The good water and sunlight conditions contribute to pressing the cost of maintaining plants and raising the profit from lettuce production. These results are important to the attention of the water and sunlight conditions that can raise lettuce production in Indonesia